FIELDS OF POTENTIAL USE OF CRYPTOCURRENCIES IN THE PAYMENT SERVICES MARKET IN POLAND – RESULTS OF AN EMPIRICAL STUDY - Anna Iwona Piotrowska (Copernican Journal of Finance & Accounting, 2017)
The payment services market in Poland is particularly open to new payment solutions. The most important financial innovations of the recent years include cryptocurrencies. Bitcoin is the most well-known of them and its applications cover payments and investments. The article aims to determine the potential for using cryptocurrencies in individual segments of the payment services market in Poland. The paper considers the following research hypothesis: Representatives of the financial sector see a potential for a widespread use of cryptocurrencies in the payment services sector in Poland. The aim of the paper was achieved and the hypothesis verified on the basis of selected results of a survey among representatives of institutions operating in the financial market in Poland. The study, primarily carried out by the author, presents the opinions of experts representing the broadly understood community of professionals from the payment services market in Poland. Their views concern the directions in which innovations in the payment services sector may develop and the prospects for the use of cryptocurrencies in that area.